2017
DOI: 10.1177/0363546517726963
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Meniscal Allograft Transplantation With or Without Other Procedures: A Systematic Review and Meta-analysis

Abstract: Overall, there seems to be no significant difference between the postoperative PROs in terms of isolated MAT and combined MAT. However, more data are required to verify the effects of osteotomy and cartilage procedures on the clinical outcomes of MAT. We could not draw conclusions about the differences in complication, reoperation, survivorship, and failure rates between the 2 groups because we did not obtain sufficient data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 53 publications
1
46
0
Order By: Relevance
“…This is also in agreement with those previously reported series. [8][9][10][11][12][13][14] In series with a longer follow-up, 6,7 functional improvements were also observed. However, as the MRI aspect worsened and the size considerably decreased, its potential chondroprotective effect was questioned.…”
Section: Discussionmentioning
confidence: 99%
“…This is also in agreement with those previously reported series. [8][9][10][11][12][13][14] In series with a longer follow-up, 6,7 functional improvements were also observed. However, as the MRI aspect worsened and the size considerably decreased, its potential chondroprotective effect was questioned.…”
Section: Discussionmentioning
confidence: 99%
“…2 The lateral meniscus serves primarily to distribute loads; therefore, compromise of this structure can independently lead to progression of osteoarthritis (OA) in that respective compartment of the knee. 3 Therefore, lateral meniscusedeficient patients with a valgus deformity present a unique scenario of compounded risk of articular cartilage damage. 4,5 Although knee arthroplasty is considered a viable option for older patients with such pathologies, it is not an option in young patients with preserved joint space on radiographs who wish to participate in high-impact athletic activities.…”
Section: See Commentary On Page 261mentioning
confidence: 99%
“…These operations have been individually shown to provide good clinical outcomes at short-term and midterm follow-up. 3,[8][9][10] Traditionally, however, malalignment has been considered a contraindication to MAT of the ipsilateral compartment. 11,12 Recent improvements in operative techniques, surgical devices, and evidence-based treatment guidelines have allowed for realignment procedures and MAT to be performed in combination.…”
Section: See Commentary On Page 261mentioning
confidence: 99%
“…32,40,47,48 Similarly, we noted a higher postoperative Lysholm's score for isolated MAT, although there were no differences in the three other scales between the two situations. In a recent dedicated meta-analysis, Lee et al 16 found no significant differences in terms of PROMs between isolated and combined MATs.…”
Section: Discussionmentioning
confidence: 95%
“…We also identified areas in which there is need for more and better quality evidence, specifically concerning the role of preoperative chondral damage, sport level, time from meniscectomy, and smoking status, whose impact on clinical outcome is still controversial. Several systematic reviews and meta-analyses have been published in the last decade about MAT; these, however, were mostly introductory in their nature, [7][8][9][10][11][12] focused primarily on outcomes in general, 2,3,13,14 or evaluated one single predictor in detail, such as laterality, 15 the impact of concomitant procedures, 16 or the type of graft fixation. 17 Other reviewers considered particular aspects, such as the chondroprotective role of MAT 5 or the feasibility of sports activity after recovery.…”
Section: Discussionmentioning
confidence: 99%